Modificações na estrutura vertical de pastos de capim-xaraés sob lotação intermitente por bovinos - Galzerano, L.; Malheiros, E. B. [UNESP]; Raposo, E. [UNESP]; Morgado, E. S.; Ruggieri, A. C. [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to evaluate the effects of residual leaf area index (rLAI), years of evaluation and grazing cycles in the vertical structure of the canopy and the proportion of morphological components of xaraés palisadegrass pastures submitted to grazing intensities in two summers. The experiment was carried out at the Faculdade de Ciências Agrárias e Veterinária of Unesp, Campus of Jaboticabal, SP and the intensities of grazing were defined by four rLAI: 0.8, 1.3, 1.8 and 2.3. When the canopy intercepted 95% of incident light, the animals were placed on the pasture for grazing and kept until the rLAI target had been reached. Pastures were grazed by non-lactating Holstein cows (Bos taurus taurus L.) using the mob-stocking technique. the proportion of the morphological components of the pasture and the vertical structure of the canopy by the inclined point device was evaluated. Residual leaf area index from 1.3 to 1.8 are the best in relation to the vertical structure of the canopy and proportion of the morphological components of the pasture submitted to grazing intensities.
Changes in the vertical structure of xaraés palisadegrass pastures under intermittent stocking by cattle
Keywords: Brachiaria; Inclined point; LAI; Light interception; Urochloa